Spatial planning and territorial governance in Southern Europe between economic crisis and austerity policies. Issue 1 (2nd January 2020) - Tulumello, Simone; Cotella, Giancarlo; Othengrafen, Frank
ABSTRACT: This article examines how spatial planning systems have changed in Portugal, Spain, Italy and Greece in times of economic recession and austerity politics, in amid pressures of external actors, and local conditions and traditions. We analyse the round of reforms of spatial planning and territorial governance implemented by national governments under pressures by European institutions, as well as local responses to them. On the one hand, we highlight how European institutions have used the conditionalities attached to bailout packages and other instrument of pressure to frame what can be considered an implicit Southern European spatial planning policy developed by the European Union. On the other, we suggest that Southern European planning amid crisis and austerity should be understood, together, as field that problematizes the idea of Europeanization of planning; a space used as 'prototype' for new rounds of neoliberalization; and a political space that continuously develops through top-down/bottom-up dialectic conflicts.